Women, Role Failure, and the Nuclear Family in Stephen King’s The Shining - Kyra McKauffley (Spectrum, 2023)
While Stephen King’s The Shining (1997) features a hotel haunted by ghosts, the main female character Wendy Torrance is much more haunted by her fear of failing to fulfill her gender role within the structure of the traditional, white, American nuclear family. In this paper, I analyze how the fear of being an unsuccessful wife and mother illustrates structural problems within the nuclear family that are detrimental to women. Not only do they produce persistent insecurity and anxiety, but they also reinforce the delegation of power to a sole patriarchal authority figure. The Shining reveals how these issues become especially problematic in situations of abuse. However, it also presents an opportunity for women to escape from both abuse and the fear of role failure: completely abandoning the structure of the nuclear family. Thus, The Shining illuminates inherent flaws within the nuclear family’s roles and suggests that women cannot find autonomy, freedom, or happiness within its confines.